Investigation of Tangential Force, Horsepower and Material Removal Rate Associating HAAS CNC Milling, Al6061-T6511 Work Material & TiAlN Coated End Mill Tool - Sivarao, Subramonian; Fairuz, Dimin; T. , Joseph Sahaya Anand; Ahmad, Kamely (IJENS, 2010)
High speed machining has emerged to become one of the most versatile material removal processes in industries. In gaining optimum cutting conditions, the investigation of the relationship between cutting conditions and technical performance factors such as tangential forces generated during machining is of great importance. This work presents an experimental study on the material removal rate (MRR), horsepower generated at spindle and tangential forces of CNC milling machine tool at 50 mm/min federate by varying depths of cut (DOC). The objective of this research work is to relate the resultant surface roughness measured in arithmetic average mean roughness, Ra to the MRR, horsepower and tangential forces generated by each depth of cut in analyzing their respective behavior / trend. The experiments were carried out using 6 varying depths of cut beginning from 0.5mm with an increment of 0.5mm each depth until the final depth of cut reaches 3.0mm utilizing a new cutting tool at each depth. At each depth of cut, the material removal rate and horsepower were formulated to obtain the cutting forces in the form of tangential forces exerted on the Al 6061-T6511 work piece. The trend achieved from this work shows MRR, horsepower and tangential forces were all found to be increased with the amplification of cutting depth. The findings are detailed and fully presented latter in this paper.